1994
DOI: 10.1037/0022-3514.67.4.688
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the link between marital support and satisfaction in older couples.

Abstract: Bu çalışmada evlilik doyumu, eş desteği, eşe kendini açma, yaşam doyumu ve iyimserlik değişkenleri ile beraber Yapısal Eşitlik Modeli içinde test edilmiştir. Buna ek olarak, Eşe Kendini Açma Ölçeği geliştirilmiş ve evli bireylerin evlilik yıllarına, aile gelirine katkı oranlarına, çocuk sayılarına, sağlıklarından ve cinsel yaşamlarından memnuniyet düzeylerine ve ev içi sorumluluklarını paylaşımlarına göre evlilik doyumuna ilişkin profilleri incelenmiştir. Araştırmanın çalışma grubunu, 2015 yılında araştırmaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
197
4
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(239 citation statements)
references
References 70 publications
28
197
4
10
Order By: Relevance
“…Previous study suggested that woman is sensitive to find social support than man (Flaherty & Richman, 1989). Furthermore, wife also emphasizes spousal supportive behaviors in her own marital satisfaction more strongly than husband does (Acitelli & Antonucci, 1994). These findings imply that husband's positive and negative CC might be easy to find from wife 's perspective and be linked with her marital satisfaction.…”
Section: Partner Effects Of DCI On Marital Satisfactionmentioning
confidence: 50%
“…Previous study suggested that woman is sensitive to find social support than man (Flaherty & Richman, 1989). Furthermore, wife also emphasizes spousal supportive behaviors in her own marital satisfaction more strongly than husband does (Acitelli & Antonucci, 1994). These findings imply that husband's positive and negative CC might be easy to find from wife 's perspective and be linked with her marital satisfaction.…”
Section: Partner Effects Of DCI On Marital Satisfactionmentioning
confidence: 50%
“…Gable, Gonzago, and Strachman (2006) found that when individuals were supportive when talking with their partners about their partner's successes, the partners (i.e., the support recipients) rated the relationship as more satisfying. Although a positive association between receipt of support and positive relationship variables such as satisfaction, closeness, and intimacy has been found in a few studies (Acitelli & Antonucci, 1994;Hagedoorn et al, 2000), it is unclear whether the support being assessed was actual support received, perceived support, or some combination of both. Regardless, this research on support receipt and relationship variables raises the question of whether support has differential effects on individual-level variables (e.g., personal distress) when compared with relationship-level variables (e.g., relationship closeness).…”
Section: Social Support As Relationship Enhancermentioning
confidence: 99%
“…Another point is that we were not able to draw direct comparisons between countries since we did not have access to data using the same instruments from the United States, as we had in the comparison with Germany (Stevens & Westerhof, 2006). The measures involved in this study are typical of those used in large surveys (Acitelli & Antonucci, 1994;Gurung et al, 2003). Respondents were asked to identify providers and receivers of specific kinds of support, as well as companions in leisure activities, after earlier identifying members of the core network.…”
Section: Shortcomingsmentioning
confidence: 99%
“…As predicted, the husbands' marital adjustment contributed significantly to the wives' wellbeing, whereas the wives' assessment of marital quality did not predict the husbands' wellbeing. Likewise, Acitelli and Antonucci (1994) studied the link between marital support and satisfaction in older couples, in combination with their wellbeing. Receiving support from the partner, giving support to the partner, as well as the reciprocity of support exchanged contributed significantly to wives' wellbeing, whereas a negligible amount of variance in the husbands' wellbeing was explained by the same variables.…”
Section: Differential Impact Of Partner Support On Wellbeingmentioning
confidence: 99%
See 1 more Smart Citation